Problem-Based Learning Associated by Action Process Object Schema Theory in Mathematics Instruction - Achmad Mudrikah; Luki Luqmanul Hakim (Proceedings of AICS - Social Sciences, 2016)
Problem-Based Learning (PBL) Associated by Action Process Object Schema (APOS) Theory were implemented to 26 prospective mathematics teachers in the mathematics for senior high school students course. It was hypothesized that the six steps of PBL are appropriate with mental constructions of APOS that make students can reach the objectives of the course. Five main questions on recorded semi-structured interviews were applied to get the information about the implementation of PBL associated by APOS theory and students’ ability to create mathematics instruction in senior high school by using PBL associated by APOS theory. The data strongly supported this model in confirmatory factor analyses. The data also revealed the hypothesized differential relations between teacher cognitions and teacher education.